Estimating the Impact of Chinese Foreign Direct Investment on Telecommunications Penetration Rates - Peter Jiang (International Telecommunications Society (ITS), 2024)
This research examines the effects of Chinese Foreign Direct Investment (CFDI) on fixed broadband and mobile cellular penetration rates using panel data from the "China Global Investment Tracker," a dataset of publicly available CFDI transactions from 2005 to 2023. As CFDI grows to pre-COVID-19 levels, its impact on penetration rates may be influenced by the Chinese government's preferential treatment for its state-owned enterprises (SOE) and telecommunications companies. Policy makers interested in FDI liberalization would benefit from understanding the distinct consequences of FDI from different sources. Through panel data analysis, this paper estimates that CFDI has a positive relationship with fixed broadband subscriptions and a negative relationship with mobile cellular subscriptions. This paper also explores potential explanations for these trends and their policy implications.
Keywords: 330; Foreign direct investment; China; Telecommunications; Broadband; Cellular; Panel data